Neoclassical convergence versus technological catch-up: A contribution for reaching a consensus - Alain Desdoigts (Fondazione Eni Enrico Mattei (FEEM), 2002)
New macro empirical evidence is provided to assess the relative importance of object and idea gaps in explaining the world income distribution dynamics over a benchmark period 1960-1985. Results are then extended through 1995. Formal statistical hypothesis tests allow us to discriminate between two competing growth models: (i) the standard neoclassical growth model similar to that employed by Mankiw, Romer, and Weil (1992), (ii) a Schumpeterian endogenous growth model closely related to the Nelson and Phelps' approach (1966) that emphasizes the importance of technology transfer in addition to factors accumulation as an opportunity to catch up. First, the latter can hardly be rejected and reveals itself to be a reliable either alternative or complementary model depending on the sample under study. Second, taking into consideration the impact of the technological catch-up phenomenon allows us to better capture and locally fit the pattern of income distribution dynamics that took place over the period.
Keywords: C12; C14; C21; O33; O40; O5; 330; Schumpeterian growth; neoclassical convergence; technological catch-up; and income dynamics; Entwicklungskonvergenz; Technologietransfer; Wachstumstheorie; Neue Wachstumstheorie; Schätzung; Theorie; Welt